2017
DOI: 10.1155/2017/4830265
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training and Stroke: A Critical Analysis of Different Training Programs

Abstract: The aim of this study was to carry out a literature review on the overall benefits of resistance training (RT) after stroke and undertake a critical analysis of the resistance exercise programs surveyed (rest interval between sets and exercises, number of sets, number of repetitions, intensity, duration of training, and weekly frequency). To obtain articles for the review, we searched PubMed, Google Scholar, and Physiotherapy Evidence Database (PEDro). Inclusion criteria were considered using the PICO (populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 82 publications
1
10
0
5
Order By: Relevance
“…Nevertheless, researchers have argued that resistance training (RT), a type of physical exercise in which muscle contractions occur against a predetermined load [11], should receive priority attention in rehabilitation protocols for stroke survivors to maximize gains in mobility and independence [12]. A recent review of our group [12] indicated that the benefits of RT in stroke survivors go beyond the neuromuscular system and may include improvements in anxiety levels and quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, researchers have argued that resistance training (RT), a type of physical exercise in which muscle contractions occur against a predetermined load [11], should receive priority attention in rehabilitation protocols for stroke survivors to maximize gains in mobility and independence [12]. A recent review of our group [12] indicated that the benefits of RT in stroke survivors go beyond the neuromuscular system and may include improvements in anxiety levels and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies investigated RT protocols and stroke were based on exercise and isokinetic machines, limiting their external validity [12, 13]. Besides that, evidence for the effects of RT on cardiac autonomic modulation and oxidative stress markers in stroke survivors are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…O conhecimento dessa resposta do número de repetições ao longo de séries máximas com diferentes intervalos, ambos muito usados na prática do TF, nos indica que para aqueles indivíduos que fazem seus treinamentos com duas séries, quantidade já indicada como eficiente no contexto de saúde, [13][14][15][16] intervalos mais curtos podem ser usados visando otimizar o tempo de treinamento sem prejuízos substanciais no número de repetições, mantendo este em uma mesma faixa de trabalho ou de manifestação da força (8/10RM) nas duas séries. Porém, mesmo no contexto de saúde e especialmente em TF com objetivos estéticos e/ou de desempenho, no qual o número de séries indicado, [17][18][19] especialmente para não iniciantes, é de três ou mais, é importante estabelecer-se um intervalo recuperativo maior, pois nossos achados demonstram que até a terceira série, o intervalo de 2 min foi capaz de proporcionar uma recuperação suficiente para manutenção do número de repetições. Já na quarta série, mesmo a sessão com intervalo maior já demonstra redução no número de repetições em relação à primeira série.…”
Section: Discussionunclassified
“…Apesar de nosso estudo ter caráter transversal e não investigar efeitos crônicos como força e hipertrofia, é importante destacar que a busca e a valorização do volume no TF, compreendendo-se formas de estruturação do treinamento sem prejuízos na sobrecarga, se dá pelas evidências acerca da relação que essas variáveis do TF têm com esses desfechos. 6,17 Nesse contexto, destacam-se os achados de Schoenfeld et al, 6 que encontraram maiores níveis de força e melhor resultado hipertrófico com intervalos de 3 min vs intervalos de 1 min frente ao TF de 8 semanas. Este estudo também foi conduzido com homens jovens treinados em força, alocados randomicamente nos grupos de intervenção, sendo a hipertrofia muscular mensurada por imagem de ultrassom e a sobrecarga de treinamento registrada ao longo do tempo.…”
Section: Discussionunclassified
“…It is therefore important to better evaluate therapies capable of improving stroke patients' strength. For example, resistance training is promising (Ada et al, 2006;Harris & Eng, 2010) but scientific evidence suffers from a lack of standardization which prevents us from conclude on its efficacy (Gambassi et al, 2017). Therapists assessing functional strength training intervention should follow TIDieR checklist (Vliet et al, 2016).…”
Section: Using Optimal Control Laws To Improve Stroke Rehabilitationmentioning
confidence: 99%